Efektivitas Komunikasi Pemasaran Warung Pak T Pada Aplikasi Shopee Food Dalam Membangun Brand Positioning Di Benak Konsumen - Adhellia Nanda Eka Saputri; Afina Damayanti; Rahma Putri Anisya (CV. ITTC INDONESIA, 2022)
This study aims to determine the effectiveness of Warung Pak T's marketing communications on the Shopee Food application in building brand positioning in the minds of consumers. As the development of the internet has an impact on business processes where many entrepreneurs are found running their businesses using sophisticated technology. With this in mind, it is to support producers in communicating their products and aims to carry out online marketing communications. This research was conducted to get a positioning benefit where the products sold at Pak T's shop can be known by the public, especially the City of Magelang. The theory used in this study is the Integrated Marketing Communication (IMC) Theory. The type of research used is descriptive quantitative research which only describes situations or events. Researchers distributed questionnaires online via google forms with a quota sampling technique to the people of Magelang City who had purchased Warung Pak T products, as well as a sample determined by the Taro Yamane formula with a total of 100. Quantitative data was processed using SPSS. Based on the results of the research and data processing that has been carried out in the research that was obtained, the result is that communication in building Pak T's shop brand positioning in the Shopee Food application is effective. This means that Pak T's brand positioning is as a place to eat that is practical and economical in the minds of consumers.